2019
DOI: 10.1002/lno.11259
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of particle size and composition on light scattering through measurements of size‐fractionated seawater samples

Abstract: Measurements of the particulate volume scattering function, βp(ψ), at light wavelength of 532 nm, particle size distribution, PSD, and several metrics of particulate concentration and composition were made on eight contrasting seawater samples from nearshore and coastal oceanic environments including river estuary and offshore locations. Both βp(ψ) and PSDs were measured on original (unfiltered) samples and particle size‐fractionated samples obtained through filtration using mesh filters with pore sizes of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…This finding is in agreement with previous studies that proposed that sediment resuspension occurs under high winds or tides in coastal water with a shallow bathymetry [54] and that small-sized particles are usually dominated by inorganic particles [1,11]. In general, large particles are dominated by phytoplankton or algae [55]. Therefore, D v 50 may be used as an indicator for the variation of phytoplankton and inorganic particle distribution.…”
Section: Applicability To Sentinel-2 Msi Datasupporting
confidence: 91%
“…This finding is in agreement with previous studies that proposed that sediment resuspension occurs under high winds or tides in coastal water with a shallow bathymetry [54] and that small-sized particles are usually dominated by inorganic particles [1,11]. In general, large particles are dominated by phytoplankton or algae [55]. Therefore, D v 50 may be used as an indicator for the variation of phytoplankton and inorganic particle distribution.…”
Section: Applicability To Sentinel-2 Msi Datasupporting
confidence: 91%
“…For GF/F filters, the effective pore size could be even smaller as most Prochlorococcus (equivalent spherical diameter of ~0.5 to 0.7 μm) are retained on these filters (Chavez et al, 1995). While the particle retention efficiency has been shown to be consistent in general with the nominal size (Sheldon, 1972;Taguchi & Laws, 1988), particles of sizes both bigger and smaller than the pore size can pass through the filters, which could affect the interpretation of optical measurements in terms of the precise particle size distribution (Koestner et al, 2020). While keeping in mind this limitation, we will refer to the filtrate as <0.2 and < 0.7 μm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Dall'Olmo et al (2009) measured scattering at an angle of 117°for several size fractions in the tropical Pacific Ocean and found that the contribution of particles of sizes 0.2-1.0 μm shifted from dominating in oligotrophic waters to accounting for less than 50% in mesotrophic waters. Koestner et al (2020) measured the angular scattering in three size fractions, <5 μm, <20 μm, and bulk, and found that the particles of sizes <5 μm consistently produced a major or dominant contribution (~50-80%) for b bp . While these studies imply a potentially significant contribution by submicron particles, to the best of our knowledge, full angular resolution measurements of the scattering by marine submicron particles have yet to be conducted.…”
Section: Research Lettermentioning
confidence: 99%
“…However, measurements based on microscopy are time-consuming and difficult to utilize in situ, which limits their further application in field testing [ 3 ]. The light scattering technique has been used to obtain the physical information of particles, such as the overall features of size, shape, and refractive index [ 4 ]. However, light scattering is traditionally measured through bulk volume scattering, which limits its usefulness for classification [ 5 ].…”
Section: Introductionmentioning
confidence: 99%